Efficiency of Engaging Python in Teaching Discrete Mathematics: Case Study - Alani, Lamya A. Omer (Al-Nahrain Journal of Science, 2018)
This study describes how the subject of discrete mathematics can be integrated with programming techniques for the purpose of teaching. Achieving such integration which can be understood easily by the students reminds that this subject is usually taught to the first years of the academic study. Python is one of such programming language which can be easily understood and practiced compared to other language such as C++, java etc. for instance using Python does not require such effort in designing the structure of program. By providing students with a python language they could use to understand both discrete mathematics and programming effectively and efficiently in the most appropriate manner, this reduce difficulties of imagining the logical way of writing programs also give a brilliant way to rise programming skills and give a simple way to study mathematics practically not only theoretically. This paper represent a case study for teaching discrete mathematics using Python programming language to second year students at computer science department - faculty of science, University of Duhok were given practical lectures for inserting python with their theoretical discrete mathematic study.